(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article examines the problem of visual impairment as a complex biopsychosocial problem associated with changes in living conditions and the functioning of a person’s mental organization. A visual defect increases psycho-emotional stress, makes it difficult to overcome difficult situations, causes intrapsychic conflict, social maladjustment and behavioral disorders. The article also discusses life difficulties associated with spatial orientation, social integration, everyday life and self-care, as well as professional and personal self-realization for people with visual impairments. The main approaches to overcoming these difficulties include psychological correction, rehabilitation and compensation. Compensation is based on internal compensation of visual function and includes intrasystem and intersystem compensation. The article offers an overview of the main types of compensation and the levels at which compensatory processes occur.